2020
DOI: 10.3390/ani10030375
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multienzymes Dose Supplemented Continuously or Intermittently in Drinking Water on Growth Performance, Nutrient Digestibility, and Blood Constituents of Broiler Chickens

Abstract: The aim of this work was to study the continuous or intermittent impact of a multienzyme supplement on growth performance, nutrient digestibility, and blood metabolites of broilers, and to evaluate production index of dietary supplementation. A total of 315 unsexed day-old Arbor Acres broiler chicks were randomly distributed to seven treatments groups, keeping initial body weights similar, in 35-floor pens (replicates) of nine chicks per replicate (pen) and five experimental units per treatment. All experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Our choice of enzymes was informed much by literature about the common substrates found in SFM (arabinoxylans, pectins, beta-glucans etc) [11,40]. Improved BWG and FCR were observed in birds grown of 1-21 d suggesting that more benefits are achieved at the early starter phase [39]. However, these studies administered their enzymes in drinking water whereas enzymes in the current study enzymes were administered in the feed and we observed benefits at the post finisher phase.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Our choice of enzymes was informed much by literature about the common substrates found in SFM (arabinoxylans, pectins, beta-glucans etc) [11,40]. Improved BWG and FCR were observed in birds grown of 1-21 d suggesting that more benefits are achieved at the early starter phase [39]. However, these studies administered their enzymes in drinking water whereas enzymes in the current study enzymes were administered in the feed and we observed benefits at the post finisher phase.…”
Section: Discussionmentioning
confidence: 76%
“…Xylanase showed significant improvements (p < 0.05) for all studied parameters in the post finisher phase. Enzyme effects differ according diet composition (target substrate), the age of the chickens and the dose of the enzymes [39]. Our study did not analyze the fractions of the substrates; hence, we could not ascertain the specific enzymes to target predominant substrates.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some researchers have indicated that by using multi-carbohydrase and phytase enzyme complexes, it is possible to reduce dietary AME and amino acids that make feed formulation cost-effective, while preserving optimum poultry performance (Cowieson et al 2006;Francesch and Geraert 2009;Attia et al 2020). Results from previous studies typically show the need for the use of multi-carbohydrase enzymes in broilers, however, researchers pointed out the need to balance nutritional requirements with the potential capacity of the supplemented enzyme to hydrolyse the cell wall and release the needed nutrients (Adeola and Cowieson 2011).…”
Section: Performancementioning
confidence: 99%
“…In poultry diets, particularly those based on wheat and barley, the use of carbohydrases (e.g. b-glucanase and xylanase) has also been shown to have benefits, including hydrolysing non-starch polysaccharides (NSP), decreasing digesta viscosity and releasing entrapped nutrients and improving nutrient utilisation and growth performance (Masey-O'Neill, Smith, et al 2014;Attia et al 2020). However, in low viscosity corn-soybean meal-based diets (C-SBM diets), also carbohydrases may be desired to ensure breakdown the cell wall matrix, and release nutrients encapsulated in the cell wall of the corn and SBM (Slominski 2011).…”
Section: Introductionmentioning
confidence: 99%